Introductory Remarks on Max Weber’s The Economic Ethics of the World Religions - Tyrell, Hartmann (SocietàMutamentoPolitica, 2014)
In Tyrell’s view, too little attention has been paid by Weber scholars to Max Weber’s ‘Economic Ethics of the World Religions’. The principal cause is that the studies of the ‘Economic Ethics’ have remained a torso, where the Occidental part, above all, is missing. Regrettably the essay collections edited by W. Schluchter and the debate provoked by S.N. Eisenstadt regarding ‘Kulturen der Achsenzeit’ have made little difference here, but the same is also true of the volumes which have so far appeared within the Max Weber Gesamtausgabe. Tyrell’s contribution is thus concerned (on the one hand) to determine the position of the ‘Economic Ethics’ within Weber’s sociology of religion, but (on the other hand) it also seeks to show what it is that “connects” the studies of the ‘Economic Ethics’, so as to counteract the impression that, at any one moment, we are dealing with “isolated pieces of work” in the form of monographs regarding particular world religions.